Rethinking online anti-gender hate speech: legislation and public policy making - Bladini, Moa (Directions and developments in criminal justice & law, 2025)
Introduction-anti-gender hate speech -- Theoretical perspectives and democratic framework -- Visiting the sphere of regulation -- Anti-gender hate speech counteracts gender equality -- Freedom of expression as more than an individual right -- Combating anti-gender hate speech with criminal regulation -- Anti-gender hate speech regulation revisited.